Data processing through biosensors and development of simulation software in windows & RT-Linux - Razin, Kazi Mohammed; Hossain, Jonayet; Oyon, Mahmudul Hasan (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.